THE APPLICATION OF VISUAL MAPPING AS A NEW MEDIA TO SUPPORT THE ATMOSPHERE AND AMBIANCE IN MUSIC EVENTS - Tarumanegara, William (VCD: Journal of Visual Communication Design, 2020)
So many music shows are held in Indonesia. Music shows are now also decorated by Video background or known as Visual Mapping. Visual Mapping is a new medium on the stage. This makes the writer want to make an observation on the atmosphere and ambiance provided by a Visual Mapping on a music event. Qualitative methods with observative techniques and interviews to obtain data and information needed to be used as a basis for data collection. The writer expects that visual mapping observation will be able to provide an explanation regarding visual mapping as a new media that provides an atmosphere & ambiance as well as a new experience for visitors. Keyword: Music Event, Motion Graphics, Video Mapping, Ambience, Media.